Degradation and recovery in poly(butylene adipate-co-terephthalate)/ thermoplastic starch blends. (April 2017) - Marinho, Vithória A.D.; Pereira, Camila A.B.; Vitorino, Maria B.C.; Silva, Aline S.; Carvalho, Laura H.; Canedo, Eduardo L.
Abstract: The economic and social impact of the increasing waste disposal problems of conventional plastic materials are well known and promoted the search for better recyclable and biodegradable polymers, blends and compounds. Fully biodegradable blends of poly(butylene adipate- co -terephthalate) (PBAT), a synthetic copolyester, and thermoplastic starch (TPS), a natural polysaccharide, are of technical and economic interest in the quest for eco-friendly polymeric materials to substitute conventional alternatives. One of less desirable characteristics of many new biodegradable materials is their relative thermal instability (degradation) under processing conditions. In the present work, PBAT/TPS blends with up to 30% TPS were processed at different temperatures in a laboratory internal mixer, with and without the incorporation of a chain extender additive (Joncryl). The rate of change of torque during the melt processing stage, adjusted to eliminate minor temperature variations, is a very sensitive indicator of variation of molar mass due to degradation and recovery. It was found that TPS content promotes thermal degradation in the PBAT/TPS blends at levels above those observed in neat components, in a strongly composition and temperature-dependent process. The addition of 1% of the chain extender additive partially reverts the process, especially during processing at high temperature.